Up to 10 years clinical performance of zirconia ceramic and metal-ceramic fixed partial dentures: a retrospective study - Rathmann, Friederike; Pohl, Moritz; Rammelsberg, Peter; Bömicke, Wolfgang (The journal of prosthetic dentistry, 2024)
Statement of problem - Completely veneered zirconia ceramic (ZC) fixed partial dentures (FPDs) have been reported to have a higher incidence of ceramic chipping than the standard metal-ceramic FPDs. However, data from comparative long-term studies are sparse. - Purpose - The purpose of this retrospective study was to compare the long-term survival, chipping-free survival, and success of ceramic-veneered high noble metal alloy (HN), base metal alloy (cobalt-chromium alloy) (CC), and ZC FPDs and to isolate risk factors for the incidence of failure, veneer chipping, and overall complications. - Material and methods - Data from 289 study participants (58.7% women; mean age, 57.97 ±11.51 years) provided with a total of 400 FPDs comprising 197 (49.3%) HN FPDs, 121 (30.3%) CC FPDs, and 82 (20.5%) ZC FPDs fabricated from presintered 3 mol% yttria-stabilized zirconia (mean time of service, 6.85 ±3.25 years) were evaluated. Of these, 278 (69.5%) FPDs were provided by dentists and 122 (30.5%) by dental students. Five- and 10-year survival, chipping-free survival, and success rates were calculated using the Kaplan-Meier method and compared with the log-rank test. Risk factors were assessed using Cox regression analysis. The study was exploratory, so all P values were considered exploratory and descriptive. - Results - The 5- and 10-year survival rates were 94.7% and 77.8% for HN, 93.7% and 81.2% for CC, and 92.9% and 53.3% for ZC FPDs, respectively, indicating no clear difference in survival among the framework materials. The 5- and 10-year chipping-free rates were 94.1% and 82.8% for HN, 96.1% and 78.9% for CC, and 82.6% and 62.2% for ZC FPDs, respectively, indicating a difference between HN and ZC, and CC and ZC restorations. The 5- and 10-year success rates were 83.7% and 55.3% for HN, 86.5% and 51.4% for CC, and 68.9% and 30.2% for ZC FPDs, respectively, indicating a difference between HN and ZC, and CC and ZC restorations. The Cox regression model indicated framework material as an influencing risk factor for success, and this influence persisted when chipping was investigated. Compared with zirconia, the use of a metal alloy reduced the risk of chipping or the occurrence of complications by up to one-third. - Conclusions - All FPDs showed high 5-year survival rates and acceptable 10-year survival rates with no strong differences among the materials. Higher success and chipping-free rates were observed for both HN and CC restorations compared with ZC restorations. Metal frameworks had a lower risk for complications or veneer chipping than zirconia frameworks.